2022
DOI: 10.3389/fchem.2021.780626
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Analysis of Fracture Hematoma With MALDI-MSI: Specific Lipids are Associated to Bone Fracture Healing Over Time

Abstract: Background: Fracture healing is a complex process, involving cell-cell interactions, various cytokines, and growth factors. Although fracture treatment improved over the last decades, a substantial part of all fractures shows delayed or absent healing. The fracture hematoma (fxh) is known to have a relevant role in this process, while the exact mechanisms by which it influences fracture healing are poorly understood. To improve strategies in fracture treatment, regulatory pathways in fracture healing need to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 45 publications
2
2
0
Order By: Relevance
“…Already in 1980, Boskey et al showed that the ratio of different phospholipid classes insignificantly changed when comparing different time points during fracture healing . In addition, we recently published a paper describing different lipid profiles throughout fracture healing in the fracture hematoma . The observed lipid classes and most of the identified lipids overlap between our previous and current study, which signifies the importance of these classes and lipids during fracture healing.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…Already in 1980, Boskey et al showed that the ratio of different phospholipid classes insignificantly changed when comparing different time points during fracture healing . In addition, we recently published a paper describing different lipid profiles throughout fracture healing in the fracture hematoma . The observed lipid classes and most of the identified lipids overlap between our previous and current study, which signifies the importance of these classes and lipids during fracture healing.…”
Section: Discussionsupporting
confidence: 69%
“…46 In addition, we recently published a paper describing different lipid profiles throughout fracture healing in the fracture hematoma. 47 The observed lipid classes and most of the identified lipids overlap between our previous and current study, which signifies the importance of these classes and lipids during fracture healing. The observed lipid classes that contribute to the separation between the Citr and Cont group are CARs, LPCs, PCs, SM, and TGs.…”
Section: Lipid Analyses: Identified Lipids Show Distinctsupporting
confidence: 67%
See 2 more Smart Citations